Freshwater algal biofilm assemblages are more effective than invertebrate assemblages at aggregating microplastics - Joseph Barnes; Barbara Balestra; Karen L. Knee; J. Adam Frederick; Natalie Landaverde; Jesse Meiller (Heliyon, 2024)
Microplastics, plastic particles less than 5 mm in length, are a ubiquitous pollutant in the environment, but research on freshwater microplastic contamination is lacking. A possible fate of microplastics in freshwater environments is to become entangled or aggregated in biofilms, which are matrices of algae, bacteria, and micro invertebrates that grow on underwater surfaces, following a progression of settling algae, periphyton, and finally invertebrate colonization. This in-situ study at the Oasis Marina at National Harbor in Oxon Hill, Maryland, examined how the taxonomic assemblages of freshwater biofilms in the Potomac River are associated with the number of microplastics aggregated within them. Aluminum discs, acting as artificial substrate for biofilm growth, were deployed at the water's surface and at 2 m depth to survey biofilm assemblage and were sampled monthly from October 2021–October 2022. Microplastic abundances in the water column were measured every 2 weeks over the same period. Spatial and temporal trends in trapped and suspended microplastics, water quality parameters (temperature, dissolved oxygen, pH, salinity, conductivity, turbidity, ammonia, nitrate, and phosphate), and biofilm assemblages were measured and compared to explore factors affecting the abundance of microplastics and their partitioning between the water column and biofilms. Water quality had no measurable impact on microplastic abundance in the water column at either depth, but temperature was negatively correlated to microplastic abundance in biofilms. As the weather warmed and biofilms progressed to invertebrate settling, they tended to contain fewer microplastics. This may have occurred because less biologically rich biofilms, primarily composed of unicellular algal colonies, provide a favorable surface for microplastic deposition. Understanding seasonal changes in biofilm assemblage and microplastic abundance may help track the fate of microplastics in freshwater systems, particularly in their interactions with lower trophic organisms.